QUALITY IN HIGHER EDUCATION: AN ANALYTICAL APPROACH - HARRAT Ali, HABICHE Bachir & Ahmed KABOUCHE (Ziglôbitha)
Abstract : Global education is a concept that refers to the efforts made to improve the quality of education worldwide. In this research paper, we will attempt to explore a comprehensive theoretical approach to the concept of higher education, from its definition to its levels, elements, and fundamentals. It aims to provide equal educational opportunities for all individuals, regardless of their economic or geographical backgrounds. Global education encompasses the exchange of knowledge and experiences between countries, with a focus on developing and updating educational curricula to meet the needs of the modern era. It also seeks to promote sustainable education and achieve sustainable development goals through education.